Marcadores de estresse oxidativo no testículo, córtex e hipocampo e alterações comportamentais de ratos submetidos a diferentes protocolos de utilização de anabolizantes - Bueno, Andressa (2016)
In this research we observed the effects of different anabolic androgenic steroid administration for protocols (EAA), selecting two molecules, Boldenone (BOL) and Stanozolol (ST).Among the used protocols, Protocol I, represents users who want to accelerate the anabolic effects using higher than recommended doses, in a shorter period of time, the Protocol II represents groups of anabolic steroid users, who elect a moderate dose and time intermediate and protocol III, which represents users that reduce the dose and prolong the exposure time for the purpose of decreasing androgenic effects. Our findings strongly suggest that the treatment with BOL and ST affect the anxiety, dominance and aggression behavior in mice dose and time of exposuredependent. Furthermore, it is emphasized that the memory impairment induced by boldenone is correlated with the increase of acetyl cholinesterase (AChE) activity in cerebral cortex and hippocampussuggesting that a dysfunction of the cholinergic system may be involved in the mechanism of this alteration, along with the damage associated with oxidative stress as well described in our results. Simultaneously, we evaluated the impact of these treatments on the morphology and oxidative stress parameters in the testes of rats. The increased of oxidative and nitrosative stress markers was evident, as well as significant changes in the normal morphology of the testicle, which is probably associated with the presence of these reactive species.The mechanisms by which the EAA interfere with testicular physiology and behavioral changes have not been deeply studied by our group, but there is strong evidence of the involvement of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in development. Our data shows that EAA, even at low doses, might result in a neuropathological consequences. Similarly, in the testis, no protocol proved to be safe in removing the possibility of reproductive disturbances that could lead to long-term sterility.